A Combined PWM and AEM-Based AC Voltage Controller for Resistive Loads. (14th February 2022) - Peter, Geno; Praghash, K.; Sherine, Anli; Ganji, Vivekananda
Abstract : AC voltage controller using PWM technique integrated with equal area digital modulation technique and connected to resistive loads is discussed in this paper. The proposed technique reduces the harmonics in the lower order significantly and improves the power factor compared to the existing conventional line commutated voltage controllers. The voltage and current waveforms are smoothened; therefore, a sinusoidal nature is achieved. The power factor is considerably improved at the low output voltage range when compared to existing methods. The capabilities of the proposed technique are computed mathematically and simulation results are compared with the existing methods.